Prevalence and risk factors of iron deficiency anemia among the tribal residential adolescent school students of Odisha: A cross-sectional study - Jyotiranjan Sahoo; Smaraki Mohanty; Sandhya Gupta; Sandeep K Panigrahi; Sambedana Mohanty; Deepa Prasad; Venkatarao Epari (Wolters Kluwer Medknow Publications, 2023)
Background: Globally, anemia is one of the biggest public health challenges. The highest prevalence of anemia is seen among adolescents. Tribal communities are especially at a disadvantage, with several studies documenting a high prevalence of anemia among tribal adolescents. We investigated the prevalence of anemia and its associated risk factors among the tribal residential adolescent school students in Odisha. Material and Methods: In a cross-sectional survey, the prevalence of anemia was estimated by spectrophotometry among adolescents of residential schools in three predominantly tribal districts of Odisha. The severity of anemia was defined as per the World Health Organization classification for adolescents. Results: The mean age of 953 subjects was 13.07 ± 1.48 years. The prevalence of anemia was found to be 37.3%. As per the World Health Organization classification, 19.9% had mild anemia, 16.3% had moderate, and 1% had severe anemia. Consumption of Iron Folic Acid (IFA) was associated with the level of hemoglobin at a statistically significant level. Conclusion: We found that the prevalence of anemia was lower than in similar studies conducted in other parts of the country. Despite poor coverage of beneficiaries with iron and folic acid at the national level, our study showed better compliance and was associated with a significantly higher level of hemoglobin among those who consumed IFA.